Andragogical principles and adult learners in the teaching of english for specific purposes (ESP) - Blanco Navarro, Randal Esteban (2024)
Certain particularities should be considered for the teachers of English for Specific Purposes (ESP) when they instruct adult learnes is in light of adult learning theories that ESP practitioners could strategically devise lessons for adult learners. Through the years, English language teachers of diverse students may have disregarded the age factor. Minors and adults internalize knowledge and develop language skills at different paces regardless of similar teaching conditions. This bibliographic review aims at discussing andragogical principles and ways of approaching and tailoring adult English language learners during the instructional or curriculum design in ESP contexts. A brief comparison of pedagogy and andragogy yields some insightful differences between teaching minors and instructing adults. It is commendable for ESP practitioners to consider that adult learners respond differently to academic endeavors and require curricular accommodations to effectively learn this target language. Thus, devising lesson plans and classroom instruction for adult language learners compel scrutiny of some andragogy principles, and this paper summarized some of the latest research findings to tackle English language instruction for this population.